Ukrainian official names of macroscopic fungi with a colour component - Jóźwikiewicz, Przemysław (Papers in Linguistics, 2025)
The article aims to analyse Ukrainian official names of macroscopic fungi in terms of colour components in their structure. The collected material comprises almost two thousand units (plus their Latin equivalents) and was excerpted from, among others, monographs on mycology, professional articles, academic textbooks, atlases of mushrooms, fiction or websites. The research showed that for 486 Ukrainian official mushroom names, at least one of the components referred to colour. Among the collected examples, as many as 48 hues and their shades were determined. This collection should be complemented by references to colour of the type жовто-коричневий, сіро-рожевий, біло-рудіючий and others, as well as non-coordinate compounds such as двоколірний, різнокольоровий, різнобарвний and others. The hues most frequently employed in the naming process were: white (93), yellow (73), red (68), grey (48), black (42), brown (35) and dark grey (32), while the most unusual ones would include: amethyst (2), azure (2), salmon (1) or umber (3).